STRATEGI PROGRAMMING DALAM PENGEMASAN PROGRAM “HAFIZ INDONESIA 2015” RCTI UNTUK MEMPEROLEH RATING SHARE TINGGI - Kutanto, Haronas (Communication, 2017)
ABSTRACTThe aim of creation of the Hafiz program is to provide alternative displays for children. HafizIndonesia's television program features talented children in memorizing the Qur'an without anyscenarios or scripts. So the participants present themselves on the television screen as it is. Thepurpose of this research is to know the Planning Programming strategy and PackagingProgram of Hafiz Indonesia 2015 in RCTI, in order to get high share rating. This researchmethod is using qualitative and descriptive. The theory used is Fred Wibowo’s productionconcept. The results of programming strategy in production concept are (1) RCTI is strippingstrategy on big audience and checker boarding strategy when the number of audience isdecreasing, but RCTI also uses the strategy of tent poling to introduce new program. (2) Theplanning process of Hafiz Indonesia program is carried out in a mutual way, not only by theprogramming division, but starting from the analyst program. They are consisting ofprogramming divisions and other people who are members of the program committee. (3) Preproductionactivities will be aired and begun by casting ideas or ideas into an outlinecontaining an event's program. The selected resource is the person who has the credibility andknows exactly about the topic to be discussed. Theoretically, the result of this research isexpected to give a constrictive contribution to the development and assessment ofcommunication science generally and practically, it is expected to be input for interestedparties, either institution or company about "Hafiz Indonesia 2015" program and give a newcolor or inspiring to Indonesian children in this event program.Keywords : Strategy Programming, Hafiz Indonesia, RCTI, Planning, Rating Share.ABSTRAKPenciptaan Program Hafiz bertujuan untuk memberikan tayangan alternatif bagi anak – anak.Program televisi Hafiz Indonesia menampilkan anak - anak muda berbakat dalam menghafalAl-Quran tanpa ada skenario atau naskah. Jadi para peserta menampilkan dirinya di layartelevisi dengan apa adanya. Tujuan Penelitian ini mengetahui secara mendalam StrategiPrograming Pengemasan Program Acara Hafiz Indonesia 2015 di Rajawali Citra TelevisiIndonesia guna memperoleh rating share tinggi. Metode penelitian ini dengan menggunakankualitatif, Deskriptif teori yang di gunakan yaitu Konsep Produksi Fred Wibowo. HasilPenelitiannya Strategi Programming Konsep Produksi yaitu : (1). RCTI yaitu strategi stripping pada saat jumlah audiensbesar dan strategi checker boarding pada saat jumlahaudiens mengalami penurunan, namun RCTI juga menggunakan strategi tentpolinguntukmemperkenalkan program barunya (2). Proses perencanaan program Hafiz Indonesiadilakukan secara bergotong royong tidak hanya oleh divisi programming saja, dimulai dariprogram analyst. Mereka terdiri dari divisi programming dan orang-orang lainnya yangtergabung dalam komite program. (3). Kegiatan pra produksi akan ditayangkan dan dimulaidengan penuangan ide atau gagasan ke dalam outline yang berisikan gambaran program suatuacara. Narasumber yang dipilih adalah orang yang memiliki kredibilitas dan mengetahuidengan pasti mengenai topik yang akan dibahas. Secara teoritis hasil penelitian ini diharapkandapat memberikan kontribusi yang konstruktif bagi pengembangan dan pengkajian ilmukomunikasi umumnya dan secara praktis ini diharapkan dapat menjadi bahan masukan bagipihak-pihak yang berkepentingan, baik lembaga atau perusahaan mengenai Program Acara“Hafiz Indonesia 2015” dan memberikan warna yang baru atau memberi inspirasi kepadaanak-anak Indonesia dalam program acara.Kata Kunci : Strategi Programming, Hafiz Indonesia, Perencanaan, RCTI, RatingShare.